Atrial Cardiomyopathy Predicts Worse Outcome in Patients With Lung Cancer - Ren, Mengdi; Ma, Yuyan; Wei, Meng; Ning, Yuye; Liu, Hui; Shi, Xue; Yao, Yu; Guo, Fengwei (Frontiers in Cardiovascular Medicine, 2022)
Background: Reports of the clinical outcomes associated with the co-occurrence of atrial cardiomyopathy (ACM) and lung cancer (LC) are limited. Objectives: To investigate the influence of ACM on the prognosis of LC patients and related clinical determinants. Methods: Newly diagnosed LC patients from January 1st, 2015, to December 31st, 2020, were retrospectively enrolled at the First Affiliated Hospital of Xi'an Jiaotong University. The demographics and overall survival (OS) of the patients with or without ACM were compared. The survival rate was analyzed using the Kaplan–Meier method and multivariate Cox regression analysis. Binary logistic regression analysis was used to determine the risk factors for ACM. Results: A total of 306 patients (65.04±10.30 years of age, 72.88% male, 78.76% with non-small-cell lung cancer (NSCLC)) were analyzed. Overall, 53 (17.32%) LC patients had coexisting ACM. ACM patients were older (69 vs. 64, p=0.0013), had higher D-dimer levels (1.0 vs. 0.6, p=0.001), had lower serum calcium levels (2.23 vs. 2.31, p=0.001), had lower left ventricular ejection fraction (LVEF) values (67% vs. 69%, p=0.036), and had more frequent coronary comorbidity disease (16.98% vs. 8.82%, p=0.031). The median OS for patients with or without ACM was 15 months and 25 months, respectively (p= 0.018). Coexisting ACM compared to non-ACM was associated with worse OS in patients with LC (HR=1.543, 95% CI: 1.042-2.283, p= 0.030). Conclusions: Coexisting ACM is associated with undesirable survival outcomes in patients with LC. These findings could help better understand the cardiac burden in these patients and provide additional risk stratification for them.